Prenatally diagnosed congenital pyloric atresia in consecutive three siblings: a case report - Ryuta Saka; Dan Yamamoto; Seika Kuroda; Souji Ibuka; Tasuku Kodama; Toshimichi Hasegawa (Surgical Case Reports)
Abstract Background Congenital pyloric atresia (CPA) is a rare gastrointestinal anomaly frequently associated with epidermolysis bullosa (EB). Although the complications of familial isolated CPA are minor, delays in diagnosis can increase the chances of morbidity. Case presentation Three female infants born to a Japanese mother presented with CPA at birth. There was no consanguinity between the parents, and the spacing between pregnancies was 2 years in each case. All 3 siblings had a prenatal diagnosis of CPA owing to polyhydramnios and a dilated stomach, without dilatation of the rest of the gastrointestinal tract. All patients underwent reconstructive surgeries for establishing bowel continuity (Case 1, pyloromyotomy; Case 2, gastroduodenostomy in a diamond fashion; and Case 3, gastroduodenostomy in a side-to-side fashion) soon after birth. Their postoperative courses were uneventful, and they grew up healthily, without any complications. Conclusion Fetal ultrasonography is useful for diagnosing CPA prenatally. Successful prenatal diagnosis can lead to timely intervention after birth.